Cervical schwannoma- Two cases report - Rodrigues, Hugo (2012)
Schwannomas are benign neurogenic tumors arising on the myelin sheath of nerves. They are rare neoplasms that can occur anywhere in the body. Located in the head and neck in 25% to 45% of cases. Over the past two years were operated two cervical schwannomas in the Department of Otolaryngology, Hospital Garcia de Orta, of which we highlight, by its exuberance, a case of a female with right lateral neck mass, with slow growth over 10 years, documented by oropharyngeal endoscopy and neck CT, that conditioned marked dysphagia. The MRI showed a large right parapharyngeal mass (30mmx50mmx58mm), causing mass effect on vascularnervous pedicle and lateral aspect of the oropharynx. We performed resection of the mass by transcervical approach, and pathological result was schwannoma. There was no obvious neurological deficits postoperatively. The other case is a woman with a schwannoma of cervical topography similar to the first, which resulted in partial Horner syndrome postoperatively, which solved gradually.